Paenibacillus hemolyticus, the first hemolytic Paenibacillus with growth-promoting activities discovered - Ismail, S.; Teoh, T.C.; Ung, C.Y.; Alasil, S.M.; Omar, R. (Springer Verlag (Germany), 2012)
Paenibacillus spp. are Gram-positive, facultatively aerobic, bacilli-shaped endospore-forming bacteria. They have been detected in a variety of environments, such as soil, water, forage, insect larvae, and even clinical samples. The strain 139SI (GenBank accession No.: JF825470.1) from three strains of Paenibacillus isolates investigated here was chosen as the type strain of the proposed novel species. The other two similar strain isolates investigated were 140SI (JF825471.1) and 141SI (JQ734548.1). These strains were identified as members of the genus Paenibacillus on the basis of phenotypic characteristics, phylogenetic analysis and 16S rRNA G+C content. Surprisingly, these strains exhibited a strong hemolytic activity on 5% sheep blood agar. Their crude extracts also showed positive growth-promoting activities in colon cancer and Vero cell lines. To our knowledge, this is the first Paenibacillus with hemolytic and growth-promoting activities reported, and the name Paenibacillus hemolyticus for this novel species is proposed. The capability of this novel species in hemolytic and cell growth activities suggests its potential in both clinical and pharmacological implications.